The Epidemiology and Susceptibility of Candidemia in Jerusalem, Israel - Israel, Sarah; Amit, Sharon; Israel, Ariel; Livneh, Ayalah; Nir-Paz, Ran; Korem, Maya (Frontiers in Cellular and Infection Microbiology, 2019)
Invasive Candida infections pose a major public health problem worldwide and is a major cause of nosocomial bloodstream infection. Our aim was to assess dynamics in incidence, species distribution and antifungal susceptibility of candidemia episodes in Jerusalem, to better understand the epidemiology of invasive isolates and to better direct therapy. Methods We analyzed the incidence dynamics, species distribution and susceptibility pattern of 899 candidemia episodes during 2005-2016 in Jerusalem. Results The overall incidence of candidemia was relatively low of 0.62 per 1000 admissions. Candida albicans was the leading pathogen (39.4%); however, there was a shift towards non-albicans species, with Candida glabrata predominating among them (40%). As expected, more than one-third of candidemias occurred in intensive care units. However, the distribution between species varied and C. tropicalis was the leading pathogen in hematology-oncology patients. The susceptibility of isolates to antifungals remained stable throughout the years. Only a minority of Candida albicans isolates were non-susceptible to fluconazole (3.3%), however, an unexpectedly high resistance rate (37.8%) was observed in Candida parapsilosis isolates. We found an alarming rate of caspofungin resistance in Candida glabrata (33.6%) and Candida krusei (67%); this may reflect misclassification of resistance by the E-test method. Conclusions This is the first comprehensive candidemia analysis in the Jerusalem area that should serve as a basis for decision-making regarding appropriate antifungal treatment in the hospital setting. The exceptional high resistance rate amongst Candida parapsilosis emphasizes the importance of antifungal susceptibility monitoring in medical centers serving large urban areas to better direct appropriate treatment.